Pengaruh cairan lumpur organik unit gas bio terhadap persentase kandungan bahan organik dan protein kasar padatan lumpur organik unit gas bio - Mochammad Junus (Faculty of Animal Science, Universitas Brawijaya, 2015)
The purposes of this study were to analyze: 1) the constitution and characteristics of sludge, solid sludge and sludge flour derived from Biogas Unit (BGU); 2) the influence of organic sludge liquid on the percentage of organic and crude protein content of the BGU organic sludge (BGUOS). The methods used in the study were observation and randomized controlled trial experiments. Data derived from field study were analyzed descriptively while data derived from experiments were analyzed using variance analysis. Differences were shown using the smallest significance-p test with CI 95%. The results showed that organic sludge constitution were odious, the organic sludge was clotting after drying process. In addition it became powder as soft as bran after dried, powdered and brooded. The experiment showed that the composition of BGUOS liquid gave influence to the amount of organic content and crude protein in the powder constitution of BGUOS. The fifth treatment brought the optimum percentage of the organic content and crude protein. The research concluded that BGUOS constitution was detestable in its form of sludge, however it could be transformed into bran constitution by drying and brooding treatment. The optimum amount of organic content and crude protein of BGUOS bran were gained by using 5th treatment. The research suggest it is necessary to maintain BGUOS on the basis of local technology and to study the application of BGUOS solid powder or bran as fish and livestock feed. Keywords: Solid Biogas Unit Organic Sludge (Solid BGUOS), CP